2016
DOI: 10.1007/s12686-016-0580-5
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite discovery in an insular amphibian (Grandisonia alternans) with comments on cross-species utility and the accuracy of locus identification from unassembled Illumina data

Abstract: The Seychelles archipelago is unique among isolated oceanic islands because it features an endemic radiation of caecilian amphibians (Gymnophiona). In order to develop population genetics resources for this system, we identified microsatellite loci using unassembled Illumina MiSeq data generated from a genomic library of Grandisonia alternans, a species that occurs on multiple islands in the archipelago. Applying a recently described method (PALFINDER) we identified 8001 microsatellite loci that were potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recently identified phylogeographic patterns within the archipelago's endemic herpetofauna have revealed a variety of geographic correlations: skinks and geckos broadly differentiate into northern (Praslin and surrounding islands) and southern (Mahé, Silhouette, and surrounding islands) groups (Rocha et al, 2010;Rocha et al, 2011;Valente et al, 2013;Rocha et al, 2016a;Rocha et al, 2016b); while for the nonsooglossid anurans, a distinct lack of variability is shown in the multi-distributed treefrog Tachycnemis seychellensis (Maddock et al, 2014), conflicting with observed structuring in Seychelles endemic caecilians (Adamson et al, 2016;Maddock et al, 2016;Maddock et al, 2017). Our mtDNA analyses appear to confirm the relationship posited by Taylor et al (2012), namely that Silhouette and Praslin populations of So.…”
Section: Biogeographic and Conservation Implicationsmentioning
confidence: 99%
“…Recently identified phylogeographic patterns within the archipelago's endemic herpetofauna have revealed a variety of geographic correlations: skinks and geckos broadly differentiate into northern (Praslin and surrounding islands) and southern (Mahé, Silhouette, and surrounding islands) groups (Rocha et al, 2010;Rocha et al, 2011;Valente et al, 2013;Rocha et al, 2016a;Rocha et al, 2016b); while for the nonsooglossid anurans, a distinct lack of variability is shown in the multi-distributed treefrog Tachycnemis seychellensis (Maddock et al, 2014), conflicting with observed structuring in Seychelles endemic caecilians (Adamson et al, 2016;Maddock et al, 2016;Maddock et al, 2017). Our mtDNA analyses appear to confirm the relationship posited by Taylor et al (2012), namely that Silhouette and Praslin populations of So.…”
Section: Biogeographic and Conservation Implicationsmentioning
confidence: 99%
“…Despite the key attributes of the Seychelles system such as its continental origin, truly oceanic setting, and mosaic of ancient (including Gondwanan relictual) lineages and more recent overwater arrivals that make it attractive for studying evolutionary processes, the Seychelles biota remains poorly studied at the intraspecific level. Greater use of molecular techniques has underpinned a recent increase in the number of studies of phylogeographic patterns in the Seychelles [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. These studies have documented some common e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the key attributes of the Seychelles system such as its continental origin, truly oceanic setting, and mosaic of ancient (including Gondwanan relictual) lineages and more recent overwater arrivals that make it attractive for studying evolutionary processes, Seychelles biota remain poorly studied at the intraspecific level. Recently, through greater use of molecular techniques, studies of phylogeographic patterns in the Seychelles have increased (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Previous findings have uncovered some common (e.g.…”
Section: Introductionmentioning
confidence: 99%